2021
DOI: 10.3892/etm.2021.9993
|View full text |Cite
|
Sign up to set email alerts
|

Differences between myeloperoxidase‑antineutrophil cytoplasmic autoantibody (ANCA) and proteinase 3‑ANCA associated vasculitis: A retrospective study from a single center in China

Abstract: In antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitides (AAV), the two major target antigens of ANCA are proteinase 3 (PR3) and myeloperoxidase (MPO). Evidence is accumulating that there are distinct differences between patients with PR3-AAV and those with MPO-AAV. In the present study, the clinicopathological features and prognosis of patients with PR3-AAV and MPO-AAV from a single center in China were retrospectively analyzed. A total of 212 Chinese patients with AAV were recruited in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…More studies are needed to clarify to mechanism of ANCA in IgAN. Existing studies had shown that there were differences in regional population distribution and clinical characteristics among AAV patients with different ANCA types [34][35][36][37]. Compared with MPO-ANCA-positive patients, PR3-ANCA-positive patients were younger, had fewer kidney involvements, and had more extrarenal manifestations [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to clarify to mechanism of ANCA in IgAN. Existing studies had shown that there were differences in regional population distribution and clinical characteristics among AAV patients with different ANCA types [34][35][36][37]. Compared with MPO-ANCA-positive patients, PR3-ANCA-positive patients were younger, had fewer kidney involvements, and had more extrarenal manifestations [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The GPA and MPA degenerative alterations in the glomeruli and tubulointerstitia were indistinguishable. Patients with MPO-AAV had considerably more risk of end-stage renal disease than those with PR3-AAV [ 7 ].…”
Section: Introductionmentioning
confidence: 99%